Konsep Doa Sebagai Persembahan Hati Yang Murni Menurut St. Afrahat - Ngesti Febriani Daeli; Hendi Hendi (Angelion: Jurnal Teologi dan Pendidikan Kristen, 2022)
AbstractThis article examines Afrahat's perspectives on the meaning of prayer, its purpose, and what can be found in prayer. This article employs a literary style based on the book Mid Fourth Century Demonstration IV on Prayer, which is backed up by other authors, Church Fathers, and biblical sources. Afrahat's perspective on the significance of prayer is perfect, according to the author's research. Afrahat underlined that prayer is more than just an inward desire for God; it also entails perfection and oneness in God. First and foremost, prayer is an offering to God made with a pure heart. The ideal prayer gift to God is a pure heart rather than a prayer that is spoken out. Second, humans retain purity of heart through prayer through forgiving others as a precondition for prayer. Finally, there are humans. can convey their desires to God by God's will. These three things aim to fully explain the meaning of the prayer of St. Afrahat.Keywords: prayer;offerings; heart; forgive; AfrahatAbstrakArtikel ini adalah sebuah ulasan pandangan Afrahat tentang arti doa, tujuan doa dan apa yang didapatkan di dalam doa. Artikel ini menggunakan metode literatur dengan landasan buku Mid Fourth Century Demonstration IV on Prayer yang didukung oleh pandangan penulis lain, Bapa-bapa Gereja serta teks-teks yang ada di dalam Kitab Suci. Dari berbagai pandangan tentang arti doa yang ditemukan penulis, pandangan Afrahat adalah kesempurnaannya. Afrahat menegaskan bahwa doa bukan hanya sebagai sikap batin yang menginginkan Tuhan tetapi mencakup penyempurnaan dan penyatuan di dalam Allah. Pertama, doa merupakan sebuah persembahan di hadapan Allah atas dasar hati yang murni. Hati yang murni menjadi sebuah persembahan terbaik di hadapan Allah ketika berdoa daripada doa yang diucapkan dengan lantang. Kedua, Melalui doa, manusia tetap menjaga kemurnian hati dengan mengampuni sesama sebagai pra-syarat doa. Ketiga, manusia dapat menyampaikan keinginannya kepada Tuhan atas kehendak Tuhan. Ketiga hal ini bertujuan untuk menjelaskan secara lengkap arti doa dari St. Afrahat.Kata-kata kunci: Doa; Persembahan; hati; mengampuni; Afrahat